Attitude and motivation of UiTM Kedah degree students in learning english towards english communication skills / Nurazwani Ahmad and Nurul Husna Hanafiah - Ahmad, Nurazwani; Hanafiah, Nurul Husna (2013)
This study aims to determine the component of attitude and type of motivation of the students in learning English towards English communication skills. This is to know the relationship between the attitude and motivation towards learning English and English communication skills. The respondents in this research involve the students itself. English communication skills is the ability to communicate and speak in English without grammatical errors and correct sentences, speak in proper intonation and the ability to convey the information and formulate approriate responses from the audiences. The students tend to have different beliefs, feelings and behavior towards learning English. The students also feel motivate to learn English based on different factors like personal reasons, instrumental and integrative. Both factors of attitude and motivation towards learning English may influence the English communication skills. Quantitative paradigm will be used where distribution of questionnaires is proposed as method of study. A self-administered questionnaire was used as the data collection method and the data is analyzed by using SPSS 19 version.